Ultrastructural Imaging of Activity-Dependent Synaptic Membrane-Trafficking Events in Cultured Brain Slices - Imig, Cordelia; López-Murcia, Francisco José; Maus, Lydia; García-Plaza, Inés Hojas; Mortensen, Lena Sünke; Schwark, Manuela; Schwarze, Valentin; Angibaud, Julie; Nägerl, U Valentin; Taschenberger, Holger; Brose, Nils; Cooper, Benjamin H (Neuron (Cambridge, Mass.), 2020)
Electron microscopy can resolve synapse ultrastructure with nanometer precision, but the capture of time-resolved, activity-dependent synaptic membrane-trafficking events has remained challenging, particularly in functionally distinct synapses in a tissue context. We present a method that combines optogenetic stimulation-coupled cryofixation ("flash-and-freeze") and electron microscopy to visualize membrane trafficking events and synapse-state-specific changes in presynaptic vesicle organization with high spatiotemporal resolution in synapses of cultured mouse brain tissue. With our experimental workflow, electrophysiological and "flash-and-freeze" electron microscopy experiments can be performed under identical conditions in artificial cerebrospinal fluid alone, without the addition of external cryoprotectants, which are otherwise needed to allow adequate tissue preservation upon freezing. Using this approach, we reveal depletion of docked vesicles and resolve compensatory membrane recycling events at individual presynaptic active zones at hippocampal mossy fiber synapses upon sustained stimulation.